Patterns of Care in Older Patients with Squamous Cell Carcinoma of the Head and Neck: A Surveillance Epidemiology and End Results-Medicare Analysis - VanderWalde, Noam A. (2013)
BACKGROUND: There is growing evidence in the literature that older patients may not benefit from more intensive therapy for Head and Neck Squamous Cell Carcinoma (HNSCC). A growing number of patients with Head and Neck Squamous Cell Carcinoma (HNSCC) are age 65 and older; however, much of the evidence base informing treatment decisions is based on substantially younger and healthier clinical trial populations. The purpose of this study was to assess the patterns of care of older HNSCC patients to better understand how age is associated with treatment decision. METHODS: Using the Surveillance, Epidemiology, and End Results (SEER)-Medicare database (1992–2007), we identified non-metastatic HNSCC patients (n=10,867) and categorized them into treatment models: surgery vs. non-surgery, and chemoradiotherapy (CRT) vs. radiotherapy (RT). Multivariate logistic regression models were used to identify variables associated with the receipt of surgery and CRT. RESULTS: Increasing age was associated with decreased odds of receiving CRT (OR = 0.94; 95% CI 0.93–0.94) but not surgery (OR 1.00; 95% CI 0.99–1.00). Co-morbidity and race were not associated with receipt of either surgery or CRT. Utilization of CRT increased while surgery decreased between 1992 and 2007. CONCLUSION: Age may influence the receipt of CRT for older HNSCC patients. There has been an increasing trend in the receipt of CRT and a decrease in primary surgery.